Outcomes and relapse patterns of stage IB grade 2 or 3 endometrial cancer treated with adjuvant vaginal brachytherapy. Issue 1 (January 2020) - Hochreiter, Alexandra; Kelly, Jacqueline R; Young, Melissa Rasar; Litkouhi, Babak; Black, Jonathan David; Stromberger, Carmen; Higgins, Susan; Schwartz, Peter E; Damast, Shari
Abstract : Introduction: Risk factors for pelvic recurrence in early stage endometrial cancer are poorly understood. We sought to describe outcomes, patterns of failure, and risk factors for recurrence among patients with grade 2–3 endometrial cancer with deep myometrial invasion who were treated with vaginal brachytherapy as sole adjuvant therapy after hysterectomy and lymph node dissection. Methods: We retrospectively reviewed the records of stage I patients with grade 2–3 endometrioid histology and ≥50% myometrial invasion treated at an academic institution from January 2005 to December 2017. Only patients with endometrioid histology were included. Mixed histologies, including papillary serous or clear cell components, were excluded. Further exclusion criteria were International Federation of Gynecology and Obstetrics stage IB grade 1 patients, follow-up time less than 3 months, receipt of pelvic irradiation or any form of systemic therapy (chemotherapy, aromatase inhibitor). Overall survival, disease-free survival, and pelvic recurrence-free survival were calculated with Kaplan–Meier methods. Multivariable Cox proportional hazards regression was used to analyze factors associated with overall survival and disease-free survival. Results: Among 131 consecutive patients identified, 111 (85%) patients met the inclusion criteria. The majority (98.2%) underwent lymph node dissection with ≥10 lymph nodes removed in 78.9%. With a median follow-up of 36 months (IQR 12–70 months), the 3-year overall survival, disease-free survival, and pelvic recurrence-free survival were 89.6%, 90.1%, and 92.8%, respectively. Histologic grade 3, older age, and lymphovascular invasion were not associated with inferior outcomes; however, lower uterine segment involvement (p=0.031), tumor size >4 cm (p=0.024), and <10 lymph nodes removed (p=0.032) were associated with reduced disease-free survival on multivariable analysis. Pelvic recurrence occurred in 12 (11%) patients, most often in the setting of synchronous distant disease (n=9), and was significantly more likely with lower uterine segment involvement. Conclusion: Among patients with stage IB grade 2–3 endometrial cancer treated with vaginal brachytherapy, the risk factors for recurrence (larger tumor size and lower uterine segment involvement) in conjunction with established risk factors (high grade, ≥50% myometrial invasion, and lymphovascular invasion) may identify a group of high-risk patients who might benefit from pelvic radiotherapy.